Occurrence of hypertension during third‐line anlotinib is associated with progression‐free survival in patients with squamous cell lung cancer (SCC): A post hoc analysis of the ALTER0303 trial. Issue 17 (17th July 2021) - Shi, Jianhua; Chen, Guimin; Wang, Haitao; Wang, Xiuxiu; Han, Baohui; Li, Kai; Wang, Qiming; Zhang, Li; Wang, Zhehai; Cheng, Ying; He, Jianxing; Shi, Yuankai; et al.
Abstract: Background: There is a lack of targeted therapeutic options for squamous cell lung cancer (SCC). Accelerated hypertension is an issue with many targeted therapies for lung cancer. This study aimed to analyze the efficacy of anlotinib, based on progression‐free survival (PFS) and overall survival (OS) in patients with SCC, stratified by hypertension and Eastern Cooperative Oncology Group (ECOG) score. Methods: This was a post hoc analysis of a multicenter, double‐blind, phase III ALTER0303 randomized controlled trial. Only patients with SCC were included. The occurrence of hypertension during the study period was defined according to CTCAE 4.03. OS and PFS were the primary and secondary endpoints, respectively. The patients were stratified according to hypertension and ECOG score, respectively. Results: The median PFS in the patients who developed hypertension was longer than in those who did not (7.2 (95% CI: 3.5–11.0) versus 3.2 (95% CI: 1.2–5.3) months, p = 0.001; HR (95% CI), 0.4 (0.2–0.8)). In the ECOG 0 patients, the median PFS in the patients who developed hypertension versus those who did not was 5.6 vs. 1.8 months, respectively (Figure 2(d)). In the ECOG 1 patients, the median PFS in the patients who developed hypertension versus those who did not was 7.0 (95% CI: 3.0–11.0) vs. 4.8 (95% CI: 1.2–8.5) months ( p = 0.043). No statistically significant differences were found in OS in the stratified analyses. Conclusions: The occurrence of hypertension might be a clinical indicator predicting the efficacy of third‐line anlotinib treatment in patients with SCC. Abstract : In SCC patients who received third‐line anlotinib treatment, the median PFS was longer in patients who developed hypertension than in those who did not. Our results suggest that the occurrence of hypertension during treatment might be a clinical indicator predicting the efficacy of third‐line anlotinib in patients with SCC.